2018
DOI: 10.17509/jpki.v4i2.13708
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan Ibu Tentang Sibling Rivalry pada Anak Usia 5-11 Tahun di Cisarua Kabupaten Bandung Barat

Abstract: ABSTRAK Sibling rivalry merupakan persaingan antar saudara untuk memperebutkan perhatian dan kasih sayang orang tua dimana persaingan tersebut terjadi setelah kehadiran adik baru. Permasalahan yang terjadi dalam sibling rivalry adalah kurangnya waktu dan perhatian yang dimiliki oleh suatu keluarga. Angka kekerasan pada anak yang dilakukan oleh saudara kandungnya sendiri yaitu sebesar 26,2%.Pengetahuan ibu tentang sibling rivalry merupakan hal yang sangat penting karena jika tidak ditangani dengan baik anak-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
19

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 0 publications
0
9
0
19
Order By: Relevance
“…• Al-Athfal: Jurnal Pendidikan Anak, 8 (1) 2022 10 avoid violence in children caused by siblings, because sibling rivalry will continue if it is not handled properly (Andriyani & Darmawan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…• Al-Athfal: Jurnal Pendidikan Anak, 8 (1) 2022 10 avoid violence in children caused by siblings, because sibling rivalry will continue if it is not handled properly (Andriyani & Darmawan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Newborn siblings were susceptible to evoke sibling rivalry (Andriyani & Darmawan, 2018). Putri (2013) identified that 40% of children struck their sibling with tools within a year, and 82% of children lashed out.…”
Section: Sibling Rivalry During the Outbreakmentioning
confidence: 99%
“…Unfortunately, many Indonesian parents instilled that sibling rivalry is a common phase during childhood that will cease as they grow up (Putri, 2013). In the long run, neglecting sibling rivalry would fester the family system, causing several discomfort and disruption, such as competitive inheritance (Andriyani & Darmawan, 2018).…”
Section: Socio-emotional Development In Childrenmentioning
confidence: 99%
See 2 more Smart Citations